The Students’ Difficulties in Reading Comprehension at The Second Semester of English Department at Batanghari University - Egi Putra; Khidayatul Munawwaroh (JELT: Journal of English Language Teaching, 2021)
This study focuses on the difficulties faced by the second semester students of Batanghari University in reading comprehension. The purposes of the study were to find out the difficulties faced by the second semester students Batanghari University and to find out the factors of difficulties in reading comprehension. The method applied was descriptive quantitative, where the test and questionnaire were used as the instrument data collection methods. The test consisted of 15 question items divided into three kinds of test and 20 questionnaires, which were descriptive text, narrative text and recount text. Index difficulty and percentage were used to analyze the data. The result of the test showed that the majority of the second semester of Batanghari University found difficulties including answering main idea, making inference, and locating reference questions. The most difficult aspect that encountered by the second semester students of Batanghari University was finding main idea questions, because the located main idea was difficult to find. In addition, based on the students’ responses in questionnaire, they mostly got difficulties in understanding vocabulary, background of knowledge, the difficulty in understanding long sentences, lack of working memory, less motivation/attention to learning reading, lack of knowledge of strategies in reading comprehension.Keyword: Students Difficulties, Reading Comprehension.